Expoziţia foto-documentară „Război după război” / Documentary photography exhibition “War after the War” - Postică Elena (Tyragetia, 2019)
On October 19, 2018, the National Museum of History of Moldova hosted the documentary photography exhibition “War after the War. Anti-Soviet Armed Resistance in Lithuania in 1944-1953” created by the Museum of Genocide Victims of the Genocide and Resistance Research Centre of Lithuania. The event was organized by the National Museum of History of Moldova in cooperation with the Embassy of the Republic of Lithuania to the Republic of Moldova. The purpose of the exhibition is to acquaint visitors with the history of anti-Soviet armed resistance in Lithuania in 1944-1953, to tell about the courage, heroism and self-sacrifice of people who decided to defend in arms the freedom, democracy and independence of the homeland. The exhibition is informational and documentary. Separate sections of the exhibition tell the visitor about the main stages of the resistance movement, the formation of the leadership bodies, the military organization, the symbolic attributes, publications of partisans, their everyday life, dwellings, the role of women in the resistance movement, about supporters of the movement, awards and holidays of partisans, and partisans’ relations with Western countries and Lithuanian organizations abroad. For nine years, the best sons of the Lithuanian people waged a partisan war against the Soviet occupation. Over 20,500 Lithuanian partisans fell in hard battles with the Soviet army, sacrificing their lives in the name of the freedom and independence of Lithuania. The memory of them is carefully preserved by the current generation of Lithuanians. This is evidenced by numerous scientific publications, hundreds of memorial complexes, museums, monuments, and commemorative plaques dedicated to Lithuanian fighters and victims of the Soviet occupation. The aspirations for freedom, independence and democracy are the main values that Lithuania inherited from a generation that was guided by the principle “Give your homeland all that you are bound to give”.